2022
DOI: 10.1177/1071181322661376
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Background Noise on User Experience and Performance of Mixed Reality Voice Dictation

Abstract: From education to manufacturing and medicine, the Microsoft HoloLens 2 mixed reality headset has been increasingly adopted. Text entry is a core functionality of the HoloLens 2, enabling communication and search features. The device tracks hand and finger movements interacting with a virtual keyboard but is slow and cumbersome. Speech-to-text dictation is a promising alternative requiring less physical effort and time. However, the HoloLens 2 dictation performance in environmental settings with varying noise l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…The 50-min use of the AR headset in the study led to concerning levels of overall simulator sickness symptoms (M = 18.51, SD = 16.48), with significant levels of nausea (M = 11.93, SD = 12.71) as well as disorientation (M = 23.66, SD = 36.16) and oculomotor discomfort (M = 27.29, SD = 22.59) being classified as bad (Stanney et al, 1997). Despite employing different tasks, this is in line with a previous study (Sinlapanuntakul P. et al, 2022), which found similarly concerning levels of simulator sickness symptoms (M = 18.14, SD = 13.69) among participants (N = 20) using the Microsoft HoloLens 2 for 40 min. These results suggest that the duration of an AR device use may be a major contributor to the development of simulator sickness, even without verbal feedback of frustrations or discomfort caused by it (Stanney et al, 1997).…”
Section: Simulator Sickness (Ssq)supporting
confidence: 90%
“…The 50-min use of the AR headset in the study led to concerning levels of overall simulator sickness symptoms (M = 18.51, SD = 16.48), with significant levels of nausea (M = 11.93, SD = 12.71) as well as disorientation (M = 23.66, SD = 36.16) and oculomotor discomfort (M = 27.29, SD = 22.59) being classified as bad (Stanney et al, 1997). Despite employing different tasks, this is in line with a previous study (Sinlapanuntakul P. et al, 2022), which found similarly concerning levels of simulator sickness symptoms (M = 18.14, SD = 13.69) among participants (N = 20) using the Microsoft HoloLens 2 for 40 min. These results suggest that the duration of an AR device use may be a major contributor to the development of simulator sickness, even without verbal feedback of frustrations or discomfort caused by it (Stanney et al, 1997).…”
Section: Simulator Sickness (Ssq)supporting
confidence: 90%
“…To mitigate harmful effects and reflect industrial conditions, experiments were carried out wearing hearing protection, enabling realism. In summary, previous results show that the HL1 has a WER of 55% (at 70 dB(A); see [18]) and the HL2 according to [19] has an average WER of 51% (SPL 40-70 dB(A)). In this study, a WER of 37% was demonstrated at 87 dB(A) with a German text template.…”
Section: Interpretation Of Resultsmentioning
confidence: 63%
“…Analogously, comparing the performance of the gesture control on the HL1, the WER was about 0.12%; see [10]. In contrast with [19], a significant influence of the SPL on the WER was shown. Although [19] did not find a significant effect on the perceived system usability, this contribution did confirm a significant difference in performance and effort expectancy (see UTAU2 PE and EE) by manipulating the experimental orders with start error and end error conditions.…”
Section: Interpretation Of Resultsmentioning
confidence: 87%
See 2 more Smart Citations